The Effects of Market Capitalization, Trade Volume, and Profitability Ratio on the Stock Returns of Companies Listed on the IDX30 - Linggi, Elsy Taruk; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2026)
This study evaluates how market capitalization, stock trading activity, and profitability levels contribute to the movement of stock returns of issuers included in the IDX30 index. This research was conducted because previous findings showed inconsistent results due to differences in periods and limitations in the sectors studied. The independent variables used include market capitalization, trading volume, profitability ratio (ROE), and dummy variables for the Covid-19 and post-Covid-19 periods. This study uses a quantitative approach by processing panel data, which is a combination of time series and cross-section data. Based on the selection of the best model, data analysis was performed using the Common Effect Model (CEM). The results of this study explain that trading volume has a positive and significant effect on stock returns, while market capitalization and profitability ratio do not have a significant effect. In addition, the Covid-19 and post-Covid-19 period variables also have a significant effect on stock returns, indicating that changes in macroeconomic conditions also determine the movement of large companies' stock returns. These findings imply that investors need to pay attention to trading activities trading and macroeconomic conditions in investment decision-making on IDX30 stocks.